Study of acceptability for the use of postpartum intrauterine contraceptive device among women attending government general hospital, Guntur - Susmitha Thota; Mahaboob Unnisa Nasreen; Surapu Ramadevi; M Himasree (Barpeta Obstetrics and Gynaecological Society, 2023)
Background: Effective contraceptive methods are necessary to control the exploding population of India for its socioeconomic development. Postpartum intra uterine contraceptive device (PPIUCD) has a huge potential as an effective contraceptive method. The increased institutional deliveries provide women an easy access to immediate PPIUCD services. Aim: To study acceptability rate of postpartum intrauterine contraceptive device among women attending government general hospital, Guntur. Materials and methods: This was a prospective observational study conducted in the department of Obstetrics and Gynaecology, Government General Hospital, Guntur, for a period of 6 months between 1st October 2020 to 31st March 2021. Subjects were antenatal women more than 34 weeks gestational age and women in their immediate postpartum period. 300 subjects were counseled regarding PPIUCD. Using validated questionnaire including age, education, parity, awareness of PPIUCD, willingness or refusal and reasons for willingness or refusal of PPIUCD were collected and data recorded. Acceptability was defined as the number of women who agreed and got PPIUCD inserted. Results: Out of 300 subjects counseled only 96 accepted PPIUCD insertion. Acceptability rate was found to be 32%. Acceptance was more in booked subjects (44.44%) and in subjects with prior knowledge of PPIUCD (80%). Husband's refusal was the reason for refusal in 54.9%. Conclusion: Acceptability of PPIUCD was very poor in spite of PPIUCD being safe, effective and long acting with very few side effects. Proper counseling and awareness programs can increase acceptability of PPIUCD.